Vignettes in Patient Safety Volume 1 - Firstenberg, Michael S.; Stawicki, Stanislaw P. (IntechOpen, 2017)
It is clearly recognized that medical errors represent a significant source of preventable healthcare-related morbidity and mortality. Furthermore, evidence shows that such complications are often the result of a series of smaller errors, missed opportunities, poor communication, breakdowns in established guidelines or protocols, or system-based deficiencies. While such events often start with the misadventures of an individual, it is how such events are managed that can determine outcomes and hopefully prevent future adverse events. The goal of Vignettes in Patient Safety is to illustrate and discuss, in a clinically relevant format, examples in which evidence-based approaches to patient care, using established methodologies to develop highly functional multidisciplinary teams, can help foster an institutional culture of patient safety and high-quality care delivery.